DNA Binding Regions of Q Proteins of Phages λ and φ80 - Guo, Jingshu (American Society for Microbiology, 2004)
Bacteriophage λ gene Q protein and the related proteins of other lambdoid phages are transcription antiterminators that interact both with DNA in the late gene promoter segment and with RNA polymerase subunits. Using hybrids between Q of λ and the related Q of phage 80, we characterized elements of both Q and DNA that contribute to the DNA binding function. In particular, we found a C-terminal segment of the protein that is responsible for binding specificity and an ∼15 residue segment on a predicted alpha helix within this segment at which alanine substitutions decrease DNA binding. We identified a six-nucleotide segment located between the −35 and −10 promoter elements that confers binding specificity and is the site of point mutants that impair binding, and we isolated suppressors in λ Q that restore binding function by increasing the overall binding affinity. We also identified putative zinc finger structures in both proteins.